How Naturalism Refutes Itself: Pragmatist Challenges for Naturalism (William James and Charles Sanders Peirce) - Wesół, Bartosz (Studia Philosophiae Christianae, 2025)
This paper examines how radical naturalism, when defined as an ontological position grounded exclusively in the scientific method, is ultimately self-refuting. Drawing on the works of William James and Charles Sanders Peirce, I argue that both thinkers, though in different ways, pose significant challenges to naturalism. James interprets naturalism as an “overbelief,” a dogmatic worldview that is assumed rather than justified through science. Peirce, in turn, highlights the indispensable role of abduction in scientific inquiry, a conjectural process that cannot itself be naturalistically explained. When combined with Jaegwon Kim’s analysis of the epistemological and metaphysical dimensions of naturalism, these insights reveal that radical naturalism cannot justifying itself and it is also self-refuting. As a result, the scope of legitimate naturalistic positions must be reconsidered within more modest boundaries. —————————————- Zgłoszono: 23/07/2025. Zrecenzowano: 25/08/2025. Zaakceptowano do publikacji: 9/10/2025.